PERLINDUNGAN HUKUM TERHADAP WHISTLEBLOWER DALAM TINDAK PIDANA KORUPSI DI INDONESIA - Podungge, Alamsyah; Ratnawati, Elfrida (UNES Law Review, 2023)
This research examines the legal protection of whistleblowers in corruption crimes in Indonesia. The role of the reporter is very necessary or important in law enforcement. The presence of whistleblowers helps law enforcement agencies and makes them more accessible in uncovering cases of corruption criminal activity. Therefore, the state must provide legal protection to the Petitioners to protect their rights by law. Second, the state must also pay tribute to the reporter. Because the award is a form of recognition from the state to the applicants for their participation in helping law enforcement and protecting our country. Like the suspected corrupt journalists in Cirebon, they should be legally protected from prosecution. Nevertheless, he is under suspicion and the LPSK must assist in every way possible to ensure that his rights are protected or fully recognized. This study answers several questions. (1) Legal protection for reporters of corruption cases in Indonesia. (2) legal mechanisms in the criminal justice system to ensure the safety of reporters in corruption cases; This study uses social laws to study with the help of social sciences. First, the research results show that there is legal protection for reporters. This means that, based on Article 10 of Law Number 31 of 2014 concerning Protection of Witnesses and Victims, they do not only receive physical and immaterial legal protection, but also physical and psychological protection. Second, whistleblower regulations have not been regulated clearly so that special rules and legal guarantees are needed for whistleblowers to protect them from threats.